Redworm (Eisenia fetida) as largemouth bass feed - first results - Rodrigues, A.M. (2015)
Redworm (Eisenia fetida) have been found to be a very good source of protein and fat. Chemical composition are important factor in selecting redworms as aquaculture feed but the high moisture (80.97% ±0.438) and ash (8.78% ±0.149) content, mainly soil, could be an inconvenient. On September 23, 2014 twenty two juvenile largemouth bass (LB) (Micropterus salmoides) (0+ years) were caught from a small irrigation dam (N 39º49’27,89’’; W 07º26’57,92’’). Juveniles LB were stocked in three aquarium for commercial compound feed training. After 3 weeks 86.4% are well trained. During the compound feed training period the survival rate was 100%. On October 13, 2014 sixteen feed-trained individuals were randomly selected and stocked in two aquarium (8 LB per aquaria with 0,048m3 of water). LB initial average weight, average length, average K condition factor and density were similar in two aquarium. In aquaria G1 (feed redworm) and aquaria G2 (feed commercial compound) LB weight, length, K condition factor and density were, respectively, 13.62g (±3.171) and 13.40g (±3.002) (P>0.05); 10.49cm (±0.757) and 10.39cm (±0.649) (P>0.05); 1.160 (±0.043) and 1.179 (±0.082) (P>0.05); 2,27kg/m3 and 2.23kg/m3). In our laboratorial experiment, aquarium average water temperature range between 19.9ºC and 16.8ºC. Because in Portugal there are no specific commercial feed for largemouth bass we used a commercial compound for seabream (Sparus aurata) and European seabass (Dicentrarchus labrax) (protein 47.7%M; fat 17.3%; ash 10.9%; crude fiber 0.83%; moisture 6.1%). On day 88 (January 9, 2015) of this study average weight, length, K condition factor and density in aquaria G1 and aquaria G2 were, respectively, 17.57g (±4.071) and 19.19g (±4.811) (P<0.05); 10.88cm (±0.875) and 11.29cm (±0.871) (P<0.05); 1.346 (±0.051) and 1.311 (±0.061) (P>0.05); 2.93kg/m3 and 3.20kg/m3). Until now E. fetida seems to be a good feed for largemouth bass.